2020
DOI: 10.1002/cjoc.202000441
|View full text |Cite
|
Sign up to set email alerts
|

Isospecific Polymerization of Methyl Methacrylate by Intramolecular Rare‐Earth Metal Based Lewis Pairs†

Abstract: Rare-earth | Lewis pair | Tridentate ligand | Polymerization | Tacticity A series of cationic rare-earth aryloxide complexes, i.e., [LREOAr'] + [B(C 6 F 5) 4 ]-(L = CH 3 C(NAr)CHC(CH 3)(NCH(R)CH 2 PPh 2); RE = Y, Lu; Ar' =2,6-tBu 2-C 6 H 3 , 2,6-(PhCMe 2) 2-4-Me-C 6 H 2 ; Ar = 2,6-iPr 2-C 6 H 3 , 2,6-(Ph 2 CH) 2-4-iPr-C 6 H 2 ; R = H, CH 3 , iPr, Ph), were prepared and applied to the Lewis pair polymerization of methyl methacrylate (MMA). The stereoregularity of the resulting PMMA was significantly affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
8
0
3
Order By: Relevance
“…More significantly, the P i Bu 3 → B­(2,4-F 2 C 6 H 3 ) 3 solid sample was also stable for up to 6 days under an open-air condition, as revealed by the NMR spectra (Figures S16–S18). These findings thus demonstrated the bench stability of this organic LP, in sharp contrast to highly sensitive metal-based LPs reported previously. , The appreciable air/moisture tolerance is presumably due to the strong interaction between the B­(2,4-F 2 C 6 H 3 ) 3 LA and the P i Bu 3 LB, which can effectively suppress the complexation of B­(2,4-F 2 C 6 H 3 ) 3 with H 2 O and therefore shut down the subsequent decomposition of borane via B–C bond protonolysis as well as irreversible deprotonation of H 2 O → B­(2,4-F 2 C 6 H 3 ) 3 by P i Bu 3 to form deactivated compounds (e.g., [H-P i Bu 3 ] + [HO-B­(2,4-F 2 C 6 H 3 ) 3 ] − ). It is worth pointing out that a delicate balance of LA–LB interaction has been met in the P i Bu 3 → B­(2,4-F 2 C 6 H 3 ) 3 CLA, which is strong enough to render its air/moisture tolerance but also is the weakest possible so that the CLA can readily convert into an FLP in the presence of a monomer to provide sufficient orthogonal reactivity for quantitative initiation.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…More significantly, the P i Bu 3 → B­(2,4-F 2 C 6 H 3 ) 3 solid sample was also stable for up to 6 days under an open-air condition, as revealed by the NMR spectra (Figures S16–S18). These findings thus demonstrated the bench stability of this organic LP, in sharp contrast to highly sensitive metal-based LPs reported previously. , The appreciable air/moisture tolerance is presumably due to the strong interaction between the B­(2,4-F 2 C 6 H 3 ) 3 LA and the P i Bu 3 LB, which can effectively suppress the complexation of B­(2,4-F 2 C 6 H 3 ) 3 with H 2 O and therefore shut down the subsequent decomposition of borane via B–C bond protonolysis as well as irreversible deprotonation of H 2 O → B­(2,4-F 2 C 6 H 3 ) 3 by P i Bu 3 to form deactivated compounds (e.g., [H-P i Bu 3 ] + [HO-B­(2,4-F 2 C 6 H 3 ) 3 ] − ). It is worth pointing out that a delicate balance of LA–LB interaction has been met in the P i Bu 3 → B­(2,4-F 2 C 6 H 3 ) 3 CLA, which is strong enough to render its air/moisture tolerance but also is the weakest possible so that the CLA can readily convert into an FLP in the presence of a monomer to provide sufficient orthogonal reactivity for quantitative initiation.…”
Section: Resultsmentioning
confidence: 56%
“…Next, the thermal stability and air/moisture tolerance of the P i Bu 3 → B(2,4-F 2 C 6 H 3 ) 3 CLA were then evaluated. Heating a P i Bu 3 → B(2,4-F 2 C 6 H 3 ) 3 benzene-d 6 solution at 80 °C and monitoring its variation by the NMR spectra at different time intervals revealed virtually the same 1 H, 19 F, and 31 P NMR spectra up to 24 h (Figures S10−S12), indicative of the excellent thermal stability of this adduct. In addition, when using "wet" benzene-d 6 as the solvent, the NMR spectra of the P i Bu 3 → B(2,4-F 2 C 6 H 3 ) 3 sample were essentially unchanged within 24 h (Figures S13−S15).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27] It should be noted that only a few types of LBs have been discovered for this process. Currently, N-heterocyclic carbenes (NHCs), 24,28 N-heterocyclic olefins (NHOs), [21][22][23]29 and organophosphorus(III) bases (including alkyl phosphines, 30,31 imidazolin-2-ylidenamino substituted phosphines (IAPs), [32][33][34] and pyridinylidenaminophosphines (PyAPs) 35 ) have been reported (Fig. 1a), and are usually employed with organoaluminum compounds, such as AlR n (BHT) 3−n (R = Me, Et, iBu).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, LPP has attracted a great deal of attention as an emerging polymerization technique. In 2016, Rieger et al reported that a highly interacting Et 3 Al/PMe 3 Lewis pair enabled the polymerization of 4VP, albeit with a low activity . We were interested in replacing main-group-derived Lewis acids with rare-earth (RE) elements, which resulted in a typical FLP-like reactivity for RE complexes. In our previous work, we developed several intra- and intermolecular , RE-based Lewis pairs that were active for the LPP of methyl methacrylate (MMA) and its analogues. However, the intermolecular combination of a RE triaryloxide with organic phosphine, for example, PEt 3 , which was highly active toward acrylates polymerization, showed negligible activity for 4VP polymerization.…”
Section: Introductionmentioning
confidence: 99%